Racial imaginary and US literature - Constantin Agramonte, Regina de las Mercedes (2020)
The racial imaginary in the United States’ literary discourse is the object of study of this re- search, which is aiming at determining how the discourse of ilocutive agents, who are black female valuating subjects, reflects the racial imaginary of the author as a subject of the enun- ciation. Theory involving discourse, Critical Discourse Analysis, imaginaries and ideology was presented in the research. The methodology included a literary review, a literary analysis, a Critical Discourse Analysis, the historical-logical, the inductive-deductive and analytic-syn- thetic methods. Several US novels dealing with race and written by black and white authors were analyzed in order to understand the difficulties in writing about the “other” Finally, The Help was selected for the discourse analysis of black female valuating subjects due to the controversy this novel generated since its release. A dimensional analysis demonstrated that even though the racial imaginary has indeed an impact on the portrayal of the characters, this novel also has positive characteristics present in some African-American works.